STRATEGI PENINGKATAN KINERJA PENYULUH PERTANIAN DI KABUPATEN LANDAK - Eligia Paginian; Dewi Kurniati; Abdul Hamid A Yusro (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
Agricultural extension is the first gate of agricultural development to empower farmer in district of Landak. However, the result of performance is not as expected, so strategy for enhacing extension  enforcement is needed. This purpose of the research is arrange the strategies to enhace the enforcement of agricultural extension in district of Landak. Research method is a survey with qualitative approach. Respondents of the study is 47 sample person of extension, 13 farmers, 13 person of group farmers, 2 representative of deparment of agricultural in Landak district. The analysis showed that the main strength is the ability to use technology, main weakness is the number of agricultural extension is not ideal, the main opportunity is the development of technology in agriculture, the main threat is the factor of uncertain weather conditions. The strategy priority is the ST (Strength Threats) strategy, which is coaching the extension like study case that related to extension programs.